Multi-objective exploration of the launch condition for a fluctuating punted kick in rugby on the basis of PSP measurement - Seo, K.; Yorita, D.; Shimoyama, K.; Nagai, H.; Asai, K. (Procedia Engineering, 2010)
We succeeded in obtaining PSP (Pressure-Sensitive Paint) measurements for a rugby ball. It was found that the seam of the ball is the trigger for initiating low pressure. Therefore, a slower spinning ball fluctuates during flight because of the asymmetrical pressure distribution on the sides of the ball. Based on the results from PSP measurements, multi-objective optimization of the fluctuating punted kick was carried out, and then the trade-offs between the objective functions and the control variables could be visualized using Self-Organizing Maps. It was found that the higher the spin rate at launch the greater the number of fluctuations; however, the hang time becomes shorter.